Dose-Response Relationship Between Intracoronary Acetylcholine and Minimal Lumen Diameter in Coronary Endothelial Function Testing of Women and Men With Angina and No Obstructive Coronary Artery Disease. (April 2020) - Pargaonkar, Vedant S.; Lee, Justin H.; Chow, Eric K.H.; Nishi, Takeshi; Ball, Robyn L.; Kobayashi, Yuhei; Kimura, Takumi; Lee, David P.; Stefanick, Marcia L.; Fearon, William F.; Yeung, Alan C.; Tremmel, Jennifer A.
Abstract : Background: Intracoronary acetylcholine (Ach) provocation testing is the gold standard for assessing coronary endothelial function. However, dosing regimens of Ach are quite varied in the literature, and there are limited data evaluating the optimal dose. We evaluated the dose-response relationship between Ach and minimal lumen diameter (MLD) by sex and studied whether incremental intracoronary Ach doses given during endothelial function testing improve its diagnostic utility. Methods: We evaluated 65 men and 212 women with angina and no obstructive coronary artery disease who underwent endothelial function testing using the highest tolerable dose of intracoronary Ach, up to 200 μg. Epicardial endothelial dysfunction was defined as a decrease in MLD >20% after intracoronary Ach by quantitative coronary angiography. We used a linear mixed effects model to evaluate the dose-response relationship. Deming regression analysis was done to compare the %MLD constriction after incremental doses of intracoronary Ach. Results: The mean age was 53.5 years. Endothelial dysfunction was present in 186 (68.1%). Among men with endothelial dysfunction, there was a significant decrease in MLD/10 µg of Ach at doses above 50 μg and 100 µg, while this decrease in MLD was not observed in women ( P <0.001). The %MLD constriction at 20 μg versus 50 μg and 50 μg versus 100 μg were not equivalent while the %MLD constriction at 100 μg versus 200 μg were equivalent. Conclusions: Women and men appear to have different responses to Ach during endothelial function testing. In addition to having a greater response to intracoronary Ach at all doses, men also demonstrate an Ach-MLD dose-response relationship with doses up to 200 μg, while women have minimal change in MLD with doses above 50 µg. An incremental dosing regimen during endothelial function testing appears to improve the diagnostic utility of the test and should be adjusted based on the sex of the patient. Abstract : Supplemental Digital Content is available in the text.